1999
DOI: 10.1023/a:1008911101951
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This research was designed to test the hypothesis that ischemic preconditioning can be transferred between animals via whole blood transfusion. Preconditioning at a distance refers to the reduction in myocardial infarct size seen when coronary artery occlusion is preceded by brief ischemic episodes of noncardiac tissue. Isolation of the trigger signal responsible for this effect may be useful in the diagnosis and treatment of acute coronary occlusive syndromes. Rabbits were paired by crossmatching blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…There is mounting evidence that RLIC-facilitated protection is mediated by humoral factors (Dickson et al, 1999; Hess et al, 2015; Sebastian Koch, 2010; S. Koch et al, 2014; Konstantinov et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is mounting evidence that RLIC-facilitated protection is mediated by humoral factors (Dickson et al, 1999; Hess et al, 2015; Sebastian Koch, 2010; S. Koch et al, 2014; Konstantinov et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This study included exploration of a panel of blood-borne biomarkers of RLIC because there is evidence that the underlying factors responsible for the protective effects of ischemic conditioning are present in the blood (Dickson et al, 1999; Hess et al, 2015; Meller & Simon, 2015). Moreover, a recent study found that a global proteomic response was stimulated in the serum of healthy volunteers who had undergone RLIC (Hepponstall et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have demonstrated the efficacy of RIc in reducing infarct size in patients with an acute myocardial infarction (AMI), 4 , 5 in reducing myocardial damage during cardiac surgery 6 and improving long term prognosis in both patient cohorts 6 , 7 . Although the exact mechanisms underlying RIc cardioprotection are not fully understood, a number of studies suggested the involvement of both humoral 8–11 and neural signalling pathways 1 , 12–14 . Several candidate humoral factors of RIc have been proposed, including stromal cell-derived factor-1α, 15 nitrite/nitric oxide, 16 interleukin-10, 17 microRNA-144, 18 apolipoprotein A-I 19 and alpha-ketoglutarate-dependent dioxygenase Egln1 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Dickson et al. 16, 17 discovered that the ischaemic preconditioning effect could be transferred from one rabbit to another non‐preconditioned rabbit, first via whole blood transfusion, and second via transfer of coronary effluent (IPC effluent) from a preconditioned, to a naïve isolated heart. Hence, the presence and necessity of a blood‐borne cardioprotective factor is clear.…”
Section: Ric: History and Evolutionmentioning
confidence: 99%